Analysis of the Implementation of DSN-MUI No: 04/DSN- MUI/IV/2000 on Murabaha Financing at BRKS Pekanbaru Main Branch - Zahra, Salwa Nissa; Azmi, Zul (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The development of Islamic banking in Indonesia shows a positive trend as well as Riau with a majority Muslim population. Bank Riau Kepri (BRK) is a regional bank established to meet the needs of the community and support economic development in Riau Province and Riau Islands. BRK Syariah is increasingly strengthening its sharia product portfolio, including financing products. The most dominating financing account is murabaha. This study aims to analyze whether BRK Syariah has implemented murabaha financing as regulated by the DSN-MUI fatwa NO: 04/DSN-MUI/IV/2000. This research uses qualitative data where researchers conduct interviews and take references to BRK Syariah financial reports, Sharia Banking Statistics on the OJK website and literature that supports this research. The results show that BRK Syariah has implemented the DSN-MUI fatwa NO: 04/DSN-MUI/IV/2000 perfectly, except that there are several regulations that differ from the fatwa but still prioritize deliberation and mutual agreement in responding to differences.